Effects of Antipsychotic Treatment on Depressive Symptoms With Respect to Genetic Polymorphisms Related to Dopaminergic and Serotoninergic Neurotransmission in Schizophrenia Patients. Issue 5 (October 2016) - Misiak, Błażej; Frydecka, Dorota; Beszłej, Jan Aleksander; Samochowiec, Agnieszka; Tybura, Piotr; Jabłoński, Marcin; Grzywacz, Anna; Bieńkowski, Przemysław; Samochowiec, Jerzy
Abstract : Supplemental digital content is available in the text.